Respectful Pruning Improves Grapevine Development: A Case Study in Young Vineyards - Mónica Galar-Martínez; Nazareth Torres; Bárbara Sebastián; Julián Palacios; Ignacio Arzoz; Nahiara Juanena; Ana Villa-Llop; Maite Loidi; Coralie Dewasme; Jean Phillippe Roby; Luis Gonzaga Santesteban (Australian Journal of Grape and Wine Research)
Grapevine pruning is an agronomical operation required to regulate growth and yield, improve fruit quality, and maintain plant health and vigour. However, the intensification of the crop in the last decades, driven by efforts to increase productivity and decrease costs, has led to reduced attention to this operation. The aim of this study was to investigate whether different pruning styles during the first years of vineyard training affect grapevine development. Three pruning styles were followed in a newly planted cv. “Tempranillo” vineyard for four consecutive pruning seasons: (i) respectful (RESP), where pruning cuts were always made leaving protection wood between the cut and vine perennial structures, and the preferential sap flow path was chosen; (ii) aggressive (AGGR), where no protection wood was left and, when possible, the nonpreferential sap flow path was followed; and (iii) winegrape grower (WIN), where the common practices used in the area were followed, which corresponds to an intermediate style between RESP and AGGR. In general, the RESP style increased the vegetative development compared to WIN and AGGR styles over the years and produced a higher yield in the first production year, although the intensity of the effect was not the same in the two vineyards considered. This was the first effort to systematically assess the effects of respectful pruning techniques on vine vegetative growth and demonstrate scientifically its impact.